Radioactive Waste Management Strategy for a New Nuclear Power Plant - Bahčič, Eva; Naglič, Kaja; Žagar, Tomaž (Journal of Energy Technology, 2026)
An essential early phase of any new nuclear power plant (NPP) project is drafting and preparation of a radioactive waste management strategy. The paper outlines major steps in such strategy presented in a case study approach for new NPP project in Krško (the JEK2 project). The paper includes analyses of options and strategies for radioactive waste (RAW) and spent nuclear fuel (SNF) management. This article presents a proposed management plan for RAW and SNF expected to be produced during operation and decommissioning of JEK2, together with an assessment of anticipated decommissioning and waste management costs. The document further examines the existing financing framework for radioactive waste management in Slovenia, which is legally regulated for current nuclear facilities. A similar approach is planned for JEK2, including the expansion of existing and planned facilities for waste handling and storage. Accordingly, additional financial resources will be required through contributions to the national decommissioning and disposal fund. An analysis was therefore conducted to estimate the scale of additional contributions needed to ensure adequate funding for new NPP project in Krško.